Igneous Rock Associations 29. The Nenana Magnetitite Lava Flow, Alaska Range, Alaska - Reidel, S.P.; Ross, M.E.; Kasbohm, J. (Geoscience Canada, 2023)
Magnetitite deposits like El Laco (Chile) are rare and have controversial origins. An unusual magnetitite lava flow overlying a rhyolite unit occurs in the north-central Alaska Range and originally covered ~ 750 km2 of the Miocene Nenana basin. Dating of the rhyolite and relationships between the magnetitite and sedimentary rocks indicate that both are of Late Miocene age. The magnetitite flow is mainly magnetite with some post-eruptive alteration to hematite. Both the rhyolite flow and the magnetitite flow are vesicular, but the magnetitite flow also has small, millimetre-scale columnar jointing. The vesicular zones in the magnetitite flow grade into massive rock on the scale of a thin section, suggesting a degassing lava origin. Samples of the magnetitite flow contain between 12 and 26 wt.% SiO2 and between 45 and 75 wt.% FeO. Rare earth elements (REE) and trace elements from the magnetitite and rhyolite have similar patterns but with lesser abundance in the magnetitite. Both the rhyolite and the magnetitite have light-REE-enriched REE profiles with negative Eu anomalies. Electron microscopic analysis shows that most of the silica and trace element content of the magnetitite flow comes from very finely disseminated silicate minerals and glass in the magnetite. This suggests that the magnetitite was derived from a magma that had undergone unmixing into a silica-rich phase and an iron-rich phase prior to its eruption. Fractures and vesicles within the magnetitite flow contain minor rhyolitic glass and minerals suggesting that the rhyolite magma invaded columnar joints in the solidified magnetitite flow, and is a subvolcanic sill-like body at the studied locality. The magnetitite flow erupted prior to the emplacement of the rhyolite, which may be extrusive on a regional scale. The features of the Nenana magnetitite, and its geological relationships, are consistent with genetic models that invoke unmixing of magma into immiscible Fe-rich and Si-rich liquids during ascent.